Influence of calcium propionate on in vitro fermentation of sorghum-based diets - Miranda, Luis Alberto; Lee-Rangel, Héctor Aarón; Mendoza-Martínez, Germán David; Crosby-Galván, María Magdalena; Enrique Relling, Alejandro; Pinos-Rodríguez, Juan Manuel; Rojo Rubio, Rolando; González Hernandez, Milagros (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2017)
The objective of the present study was to evaluate the effect of calcium propionate (CaPr) on in vitro ruminal fermentation using a factorial arrangement 2 x 2 evaluating CaPr (0 vs. 1%) and grain level (55 vs. 65%). There was a CaPr x Grain interaction in the volume of gas produced (V; p = 0.04). Addition of CaPr prolonged Lag time (1.4 vs. 1.04 h; P<0.01), and increasing the grain level also prolonged Lag time (1.56 vs. 0.89 h; p < 0.03) and gas production rate (0.046 vs. 0.041 h-1; P<0.04). However, there were no differences in CH4, CO2, acetate, propionate and butyrate concentrations. Therefore, the addition of calcium propionate in a diet with 55 or 66% of grain increased Lag phase but it is not affected fermentation pattern or methane losses.